Yield Performance of Locally Selected Cocoa Clones in North Luwu - Agung Wahyu Soesilo; Indah Anita Sari; Imran . (Indonesian Coffee and Cocoa Research Institute, 2015)
Participatory selection in North Luwu District selected some locally cocoa clones, of which MCC 01 and MCC 02 the most promising to be developed as clonal material. This research has objectives to observe the stability performance of yield of these clones that enable be characterized of the potency as the basis for recommendation. Observation were carried out in 35 selected-farms be differentiated according to clone’s type, namely MCC 01, MCC 02 and Sulawesi 01 (control) and the year of planting (age). These farms were establised at the main area of cocoa in North Luwu. The assessed variables were the number of pod, yield components, the resistance to cocoa pod borer (CPB), vascular-streak dieback (VSD) and phytophthora pod rot (PPR). Data were recorded through 20 sampled-trees per farm in the period of April 2013 to April 2014 with monthly basis assessment. Data were analyzed refer to Eberhart & Russel method to perform stability parameters of the yield. The results indicate that these clones stable performing yield potency among plant age. MCC 01 and MCC 02 performed yield potency in amount of 3,682 kg/ha and 3,132 kg/ha respectively higher than Sulawesi 01 of 2,772 kg/ha. Evaluation of the resistance, MCC 01 having moderate resistance to CPB and VSD and resistance to PPR, however MCC 02 having resistance to CPB, VSD and PPR. Referring to the potency thus MCC 01 and MCC 02 were legally recommended as clonal material for farmers, restricted at the agroclimatic area similar to the condition in North Luwu.